Des contradictions au décrochage : récits de parcours en adaptation scolaire - Maryvonne Merri; Annie Dubeau (Nantes Université, 2023)
This article describes the interpretations of their experience in special education in Quebec by 18 young adults who have dropped out and the contradictions they experienced in these devices. The participants were met during biographical interviews. The contradictions expressed are analyzed at three stages of the school career: at the time of orientation in special education, in relation to the means implemented (notebooks, activities...) and at the time of the final dropout. Following Yrjö Engeström, the school system is located in the socio-historical context of capitalism and within a set of activity systems. Four expressions of contradictions are distinguished: conflicts, internal conflicts, dilemmas and double binds. The results show a general depreciation of the devices at the time of orientation, the loss of the exchange value of school activity, an injunction to personal rhythm as a double bind and the scarci-ty of experiences of agency in school and in the final dropout. Participants from "behavioral difficulty" classes are characterized by a social critique of the exclusion and segmentation of school audiences.